Evaluasi Kebijakan Penyelenggaraan Program Paskibraka Tingkat Provinsi Di Daerah Khusus Jakarta Tahun Anggaran 2024 - Miftackul Huda; Dedeh Mariyani; Mutia Rahma (CV. Ulil Albab Corp, 2026)
Narcotics crimes are a serious concern in the Indonesian criminal justice system due to their widespread impact on individual health and public safety. This study aims to analyze the judge's considerations in issuing sentences below the minimum limit stipulated in Law Number 35 of 2009 concerning Narcotics in the Salatiga District Court Decision No. 90/Pid.Sus/2019/Pn Slt. The method used is legal research using both a statutory and case-based approach. The results show that the judge considered several mitigating factors, including the relatively small amount of narcotics, the defendant's role as a non-major dealer, and the defendant's track record of prior involvement in similar crimes. The judge's considerations are an important instrument in realizing substantive justice and demonstrate the flexibility of the application of narcotics criminal law according to the facts of the trial.